2002
DOI: 10.1007/s00784-002-0183-2
|View full text |Cite
|
Sign up to set email alerts
|

All-ceramic crowns: bonding or cementing?

Abstract: Despite the wide variety of all-ceramic systems available today, the majority of dental practitioners hesitate to recommend and insert all-ceramic crowns. This article regards the nature of the ceramic materials, the principles of bonding and adhesion, and the clinical problems of the acid-etch technique for crowns. Advantages and disadvantages are discussed, and the influences of different factors on the strength of all-ceramic crowns are presented. Finally, the conclusion is drawn that conventional cementing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 61 publications
0
27
0
5
Order By: Relevance
“…Introduction of the acid etched ceramic protocol for bonding to enamel in 1980 [1][2][3] and the dentin adhesives in the early 1990s 4,5) , facilitated dental rehabilitation with all-ceramic prosthesis 6) . Lithium disilicate is a glassy ceramic that consists of quartz, lithium dioxide, phosphor oxide, alumina, potassium oxide and other components 7) .…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of the acid etched ceramic protocol for bonding to enamel in 1980 [1][2][3] and the dentin adhesives in the early 1990s 4,5) , facilitated dental rehabilitation with all-ceramic prosthesis 6) . Lithium disilicate is a glassy ceramic that consists of quartz, lithium dioxide, phosphor oxide, alumina, potassium oxide and other components 7) .…”
Section: Introductionmentioning
confidence: 99%
“…sclerotic processes and the deposition of secondary and tertiary dentin 14) , structural differences between radicular dentin and coronal dentin 15,16) or the presence of provisional cements, endodontic sealers, and rinsing solutions 17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…In general, conventional cements offer some advantages over resin cements, including lower costs and less complicated procedures with less opportunities for procedural errors 14,19,20) . Recent studies indicated, that the maximum resistance to fracture of endodontically treated teeth with minor loss of hard tissue is provided by the circular covering crown and that it cannot be raised by additional placement of any kind of post 21) .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8] These methods use the acute single loading failure as the test methods; however, a lifetime of dental restorations is limited by the accumulation of contact damage during oral function, and the strength of dental ceramics are significantly lower after multi-cycle loading than after single-cycle loading. 6,9 Fatigue is described as a change of material characteristics over time under cyclic conditions. 6,10 For dental ceramics, microscopic surface flaws and defects, which may develop as a result of thermal, chemical or mechanical processes, act as localized stress concentrators.…”
Section: Introductionmentioning
confidence: 99%